2002
DOI: 10.1097/00006842-200205000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Preventive Proactivity on Quality of Life of the Old-Old

Abstract: Among the old-old, exercise had long-term and multifaceted benefits over an 8-year period. Tobacco avoidance also contributed to long-term positive outcomes. These results lend support to the long-term preventive value of health-promoting proactivity spontaneously engaged in by old-old persons proposed in the framework of the PCP model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 42 publications
4
56
1
1
Order By: Relevance
“…Recent empirical results regarding physical activity on cognitive function are contradictory up to now (Anstey and Christensen 2000). Most studies Wnd a protective value regarding the development of dementia symptoms (YaVe et al 2001;Churchill et al 2002;Kahana et al 2002;Lindsay et al 2002). However, Colcombe and Kramer (2003) conducted a meta-analysis of 18 studies and found selective eVects on cognitive functions (eVect sizes between 0.2 and 0.7).…”
Section: Discussionmentioning
confidence: 99%
“…Recent empirical results regarding physical activity on cognitive function are contradictory up to now (Anstey and Christensen 2000). Most studies Wnd a protective value regarding the development of dementia symptoms (YaVe et al 2001;Churchill et al 2002;Kahana et al 2002;Lindsay et al 2002). However, Colcombe and Kramer (2003) conducted a meta-analysis of 18 studies and found selective eVects on cognitive functions (eVect sizes between 0.2 and 0.7).…”
Section: Discussionmentioning
confidence: 99%
“…Only one empirical study has used the Kahanas' model as a theoretical basis and has examined the role of preventive strategies for success. Results from a longitudinal study showed that the quality of life of 357 older adults aged 72 to 98 who engaged in several preventive health behaviors, such as exercising and giving up smoking, was enhanced after 8 years (Kahana et al, 2002).…”
Section: Proactive Coping and Successful Agingmentioning
confidence: 99%
“…Yet, when older individuals are able to maintain a certain amount of investment behaviour, this clearly will have a positive effect on their overall wellbeing. For example, as Kahana et al (2002) have shown, proactive prevention activities in older people have positive consequences for longevity, as well as for indicators of subjective wellbeing. Although there are only a few studies that have investigated investment behaviour in ageing individuals, other studies have closely examined related aspects of future orientation and planning in older people.…”
Section: Investment Behaviourmentioning
confidence: 99%